Polarization Music Function of Bia in Context of Social Change in Culture in Community Village South District Likupang South Regency of North Minahasa North Sulawesi - Kapoyos, Richard Junior; Sumaryanto F, Totok; Utomo, Udi (Universitas Negeri Semarang, 2017)
The phenomenon in the Batu village community needs to be closely examined given that the bia music of the past to present is shifting and changing, due to the lack of awareness, the behavior of the society towards the Bia music. The music of this tradition is very apprehensive to see the reality of the players from year to year diminishing in quantity and quality, not many people who can play and who can play it most aged 40 years and above. The disinterest of the young generation of traditional music with the presence of communication and entertainment technology has made it easier for people to choose various types of entertainment in accordance with what they like. The theory used in this research is the theory of socio-cultural change, data collection techniques used are: interviews, observation and documentation. The data validity technique is based on the credibility criteria, using data triangulation. The result of the research shows that polarization of changes in bia music is seen in previous music functions as ritual media and communication media, now transformed into evangelism media, cultural festivals events, association, entertainment, publicity, and education and in socio-cultural changes occur Due to internal factors caused by the artist itself as a result of the musical demands into an innovation and creativity, and external factors caused by the influence of outside culture that entered and easily accepted by the community.